2005
DOI: 10.4103/0255-0857.16056
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary Paragonimiasis mimicking Pulmonary Tuberculosis - A Report of Three Cases

Abstract: Paragonimiasis is an important cause of pulmonary disease worldwide. Infection in humans mainly occurs by ingestion of raw or undercooked freshwater crabs or crayfish. The disease is well known in endemic regions of Asian countries, where culturally based methods of food preparation foster human transmission. Three patients with clinical and radiological features compatible with pulmonary tuberculosis had been treated for tuberculosis without remedy despite an inability to demonstrate acid fast bacilli in sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It has been estimated that between 50 and 70% of patients with paragonimiasis may initially be thought to have tuberculosis and erroneously receive antituberculous therapy (76,80,129,167). This has also been described by other authors (164,165). There are a number of important sequelae associated with the misdiagnosis of tuberculosis.…”
Section: Vol 22 2009 North American Paragonimiasis In the Global Comentioning
confidence: 77%
“…It has been estimated that between 50 and 70% of patients with paragonimiasis may initially be thought to have tuberculosis and erroneously receive antituberculous therapy (76,80,129,167). This has also been described by other authors (164,165). There are a number of important sequelae associated with the misdiagnosis of tuberculosis.…”
Section: Vol 22 2009 North American Paragonimiasis In the Global Comentioning
confidence: 77%
“…In India, many of the human paragonimosis cases were reported from North Eastern states of the country and hence these states were considered to be endemic for the disease. The first human case was reported from Manipur in 1981 (Singh et al, 1982(Singh et al, , 1993(Singh et al, , 2004(Singh et al, , 2005Singh and Vashum, 1994), followed by another report from Maharashtra in 1984 (Patil et al, 1984). Later, several cases were reported from Manipur itself (Singh et al, 1986).…”
Section: Advances In Animal and Veterinary Sciences December 2015 | Vmentioning
confidence: 99%
“…Oloyede et al reported that the roentgenographic features of both pulmonary paragonimiasis and pulmonary tuberculosis identified in their study were mostly parenchymal and were similar [153]. The main differential diagnosis of cavitating pulmonary infiltrates includes bacterial abscess, tuberculosis, fungal infections, nocardiosis, and parasitic lung diseases [157]. Computerized tomography of the chest is found as a better technique compared to the chest roentgenogram by visualization of burrows and tunnels joining the Paragonimus cystic lesions [150].…”
Section: Pulmonary Paragonimiasismentioning
confidence: 99%